Emotional Intelligence under Stress: Valuable or Overrated ? (Global Journal of Human-Social Science, 2016)
Stress has created a vigorous discourse among researchers of various fields and considered as one of the most vital issue that has not yet been solved. A growing interest has been developed on the influence of emotional intelligence in reducing stress level among students. This study examined emotional intelligence as four interrelated processes which were postulated from the four-branch emotional intelligence theory of Salovey and Mayer. A selfreported measure of the Assessing Emotions Scale (AES) and the Perceived Stress Scale was used respectively to measure emotional intelligence and stress level of the participants involved. PLS-SEM was employed to assess the measurement construct and structural model of this study. The findings indicated a significant negative relationship between the ability to perceive emotion, the ability to manage one's own emotion, and the ability to manage others emotion with stress. However, no significant association were identified between the ability to utilize emotion and stress among the participants involved. Results also confirmed that the ability to perceive and assess emotion accurately as the most prominent emotional intelligence dimension in predicting stress. The applied utilities of emotional intelligence are discussed and the potential value of integrating emotional intelligence in formal tertiary education systems is also highlighted.
Keywords: emotional intelligence; perceived stress; partial least squares; path modeling